A Rare Case of Hypertrophic Cardiomyopathy with Subendocardial Late Gadolinium Enhancement in an Apical Aneurysm with Thrombus - Yusuke Morita; Takao Kato; Mitsumasa Okano; Kanae Su; Masahiro Kimura; Eri Minamino; Eisaku Nakane; Toshiaki Izumi; Shoichi Miyamoto; Tetsuya Haruna; Moriaki Inoko (Case Reports in Radiology)
The mechanisms responsible for the development of apical aneurysms in cases of hypertrophic cardiomyopathy (HCM) are currently unclear but likely involve multiple factors. Here, we present a case of HCM with marked subendocardial fibrosis involving the apical and proximal portions of the left ventricle. A 71-year-old man with left ventricular hypertrophy presented with signs and symptoms of heart failure. The presence of asymmetrical left ventricular hypertrophy and bilateral, thickened ventricular walls with an apical aneurysm on transthoracic echocardiography suggested a diagnosis of HCM with ventricular dysfunction. No intraventricular pressure gradients with obstruction were identified. Late gadolinium enhancement (LGE) with cardiac magnetic resonance imaging and endomyocardial biopsies showed subendocardial fibrosis involving the apical aneurysm and proximal portion. Whereas LGE in a transmural pattern is commonly observed in HCM apical aneurysms, subendocardial LGE, as noted in the present case, is a relatively rare occurrence. Thus, the present case may provide unique insights into the adverse remodeling process and formation of apical aneurysms in cases of HCM.